2005
DOI: 10.1097/01.qai.0000179464.40948.b9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and Risk Factors for Clinically Significant Methicillin-Resistant Staphylococcus aureus Infection in a Cohort of HIV-Infected Adults

Abstract: The incidence of initial CS-MRSA events increased more than 6-fold in a 4-year period. The associations between CA-MRSA infection and HIV severity indicators merit examination in other cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
9
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(135 citation statements)
references
References 25 publications
8
116
9
1
Order By: Relevance
“…Several studies have reported an increased risk of MRSA colonization and infection in HIV-infected individuals compared with the general population [28][29][30][31][32]. The prevalence of MRSA in Denmark is low [16] and, correspondingly, rates were low among HIV-infected individuals and comparable to those in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an increased risk of MRSA colonization and infection in HIV-infected individuals compared with the general population [28][29][30][31][32]. The prevalence of MRSA in Denmark is low [16] and, correspondingly, rates were low among HIV-infected individuals and comparable to those in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…8 CA-MRSA strains typically carry the staphylococcal chromosomal cassette mec (SCCmec) type IV or V resistance determinant conferring methicillin resistance, the Panton-Valentine leukocidin (PVL) genetic determinant and are more susceptible to non-b-lactam antibiotics than hospital-associated strains. [9][10][11] Risk factors for CA-MRSA, derived from early outbreak reports, [12][13][14][15][16][17][18][19][20] are notably different from risk factors for health care-associated MRSA (HA-MRSA). 5 Although early outbreak reports of CA-MRSA were generally confined to specific populations, CA-MRSA has now established itself in the United States and other jurisdictions 21 as the predominant pathogen causing purulent skin and soft tissue infections (SSTIs).…”
Section: Ré Sumémentioning
confidence: 99%
“…In recent years, methicillin-resistant Staphylococcus aureus (MRSA) infection has emerged as a significant complication among HIV-infected subjects [10][11][12][13][14].…”
mentioning
confidence: 99%